Respons Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq.) terhadap Pemberian Kompos Sampah Pasar dan Pupuk NPKMg (15:15:6:4) di Pre Nursery - Martua Markus Tambunan; Toga Simanungkalit; T. Irmansyah (Universitas Sumatera Utara, 2015)
The purpose of the study was to determine the growth response of oil palm seed on waste market compost and Npkmg (15:15:6:4) fertilize aplication in pre nursery. The research was conducted atthe experimental field Agricultural Faculty, Sumatera Utara University about ± 25 metres above sealevel from April to July 2014. The design use randomized block design with 2 factors treatment.The first factor was The waste market compost with 4 levels: 0 g/polybag (K);50 g/polybag (K1); 100 g/polybag (K2); 150 g/polybag (K) and the second factor was NPKMg (15:15:6:4)fertilizer with 4 levels: 0 g/polybag (P03); 2,5 g/polybag (P1); 5 g/polybag (P) and 7,5g/polybag(P32). The results showed that the waste market compost treatment has significantly effectto the plant height, total wide leaf, dry weight root and soil pH , however no significantly affectedfor, stem diameter, leaf number, length of the root, fresh weight of crown, dry weight of crown, andfresh weight of root. The NPKMg (15:15:6:4) fertilize treatment showed significant effect to stemdiameter, total wide leaf, fresh weight of crown and dry weight of crown however no significantlyaffected for plant height, leaf number, lenght of the root, fresh weight of root, dry weight of rootand soil pH. The interaction of both of treatmet showed significan for the plant height and totalwide leaf. Keywords: Oil palm, waste market compost, NPKMg (15:15:6:4) fertilizers. 0